Chronic prostatitis/chronic pelvic pain syndrome impairs erectile function through increased endothelial dysfunction, oxidative stress, apoptosis, and corporal fibrosis in a rat model. (27th August 2016) - Hu, Y.; Niu, X.; Wang, G.; Huang, J.; Liu, M.; Peng, B.
Summary: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is an independent risk factor for the development of erectile dysfunction (ED). But the molecular mechanisms underlying the relationship between CP/CPPS and ED are still unclear. The aim of this study was to investigate the effect of CP/CPPS on erectile function in a rat model and the possible mechanisms. A rat model of experimental autoimmune prostatitis (EAP) was established to mimic human CP⁄CPPS. Then twenty 2‐month‐old male Sprague–Dawley rats were divided into EAP group and control group. Intracavernosal pressure (ICP) and mean arterial pressure (MAP) were measured during cavernous nerve electrostimulation, the ratio of max ICP/MAP was calculated. Blood was collected to measure the levels of serum C‐reactive protein (CRP), tumor necrosis factor‐α (TNF‐α), interleukin‐1β (IL‐1β), interleukin‐6 (IL‐6) and testosterone, respectively. The expression of endothelial nitric oxide synthase (eNOS), cyclic guanosine monophosphate (cGMP) levels, superoxide dismutase (SOD) activity and malondialdehyde (MDA) levels in corpus cavernosum were detected. We also evaluated the smooth muscle/collagen ratio and apoptotic index (AI). The ratio of max ICP/MAP in EAP group were significantly lower than that in control group. The levels of serum CRP, TNF‐α, IL‐1β, and IL‐6 in EAP group were all significantly higher than these in control group. The expression of eNOS and cGMP levels in corpus cavernosum of EAP rats were significantly downregulated. Furthermore, decreased SOD activity and smooth muscle/collagen ratio, increased MDA levels and AI were found in corpus cavernosum of EAP rats. In conclusion, CP/CPPS impaired penile erectile function in a rat model. The declines of eNOS expression and cGMP levels in corpus cavernosum may be an important mechanism of CP/CPPS‐induced ED. CP/CPPS also increased oxidative stress, cell apoptosis and decreased smooth muscle/collagen ratio in corpus cavernosum of rats, which were all important for erectile function.